2009
DOI: 10.1007/s10577-009-9079-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical mapping of the elephant X chromosome: conservation of gene order over 105 million years

Abstract: All therian mammals (eutherians and marsupials) have an XX female/XY male sex chromosome system or some variant of it. The X and Y evolved from a homologous pair of autosomes over the 166 million years since therian mammals diverged from monotremes. Comparing the sex chromosomes of eutherians and marsupials defined an ancient X conserved region that is shared between species of these mammalian clades. However, the eutherian X (and the Y) was augmented by a recent addition (XAR) that is autosomal in marsupials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 38 publications
5
29
0
Order By: Relevance
“…The finding that genes on the human X all lie also on the elephant X chromosome implies that the fusion occurred before the eutherian radiation about 105 MYA 63. And the finding that in elephants, XCR and XAR are separated by the centromere, suggests that the two ancestral blocks underwent centromere‐centromere (Robertsonian) fusion 64.…”
Section: Sex Chromosome‐autosome Fusion Accompanied Evolution Of Euthmentioning
confidence: 99%
“…The finding that genes on the human X all lie also on the elephant X chromosome implies that the fusion occurred before the eutherian radiation about 105 MYA 63. And the finding that in elephants, XCR and XAR are separated by the centromere, suggests that the two ancestral blocks underwent centromere‐centromere (Robertsonian) fusion 64.…”
Section: Sex Chromosome‐autosome Fusion Accompanied Evolution Of Euthmentioning
confidence: 99%
“…Like the mammalian X (Ohno 1967;Rodríguez Delgado et al 2009;Ross et al 2005), synteny of avian Z-borne genes is highly conserved across species (Nanda et al 2008;Shetty et al 1999). In therian mammals, the chicken Z corresponds to autosomal regions: parts of chromosomes 5, 9, and 18 in humans and to parts of opossum chromosomes 3 and 6 (Figs.…”
Section: Sex Chromosomes In Amniotesmentioning
confidence: 99%
“…This suggests that the eutherian X arose by fusion of an ancestral autosome with the therian X between 148 MYA, when marsupials and eutherians last shared a common ancestor and 105 MYA before eutherians radiated. The position of the centromere at this junction on the X of the African elephant, Loxodonta africana, implies that there was a centric fusion in the ancestor of eutherians, followed by a centric shift in the ancestor of other eutherian lineages (Rodríguez Delgado et al 2009). …”
Section: Relationship Between Fused Regions In Sex Chromosomesmentioning
confidence: 99%
“…It was proposed that the marsupial X represents the ancestral mammal X, to which an autosomal region was fused between 160 MYA, when marsupials and placentals diverged, and 105 MYA, when placentals radiated (Graves 1995). A recent study of the elephant X chromosome (Rodriguez Delgado et al 2009) showed a correspondence between the order of genes on the human and elephant X, but placed the boundary of the conserved and added regions right at the centromere: this suggests that an original Robertsonian fusion occurred, and Afrotheria retain the original centromere; however, the ancestor of other mammals underwent a centric shift (Fig. 2).…”
Section: Kangaroo Sex Chromosomesmentioning
confidence: 99%